EXPLORING CUSTOMER VALUE IN NON APPAREL TEXTILE SMES: THE ROLE OF BUSINESS STRATEGY - Abdullah, Fadil; Putri, Safira Hutama; Maharani, Nadiya; Barus, Wan Habibi Rahman; Candrawati, Nia; Ihsan, Muhammad Alif (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study explores the relationship between business strategy, business performance, innovation, and competitive advantage and their impact on customer value for non-apparel textile SMEs in Indonesia. Using Structure Equational Modeling (SEM), it aims to understand how business strategy affects business performance and innovation and how business performance and innovation mediate the relationship between business strategy and competitive advantage. In addition, it investigates the role of competitive advantage as a mediator in increasing customer value.The results show that business strategy has a significant impact on business performance, innovation, and competitive advantage. Competitive advantage proved to be an important mediator in improving customer value. However, business performance and innovation are not always effective in mediating the relationship between business strategy and competitive advantage or customer value. The findings indicate that while business performance and innovation are important, they should be viewed as part of a more holistic approach to business strategy.This research concludes that companies should focus on strategies that integrate competitive advantage through various elements, such as innovation, product quality, and marketing. Good strategic planning and effective implementation are key to achieving and maintaining competitive advantage and increasing customer value. The findings provide important insights into the need for a holistic strategic approach to achieve long-term success in an increasingly competitive market.